Utilización de herramientas digitales en docentes de la facultad de ciencias de la educación y humanidades de la Universidad Nacional de la Amazonía Peruana de Iquitos 2022 - Lage del Castillo, Paulo Nazzir (2023)
This study has as main objective to describe the use of digital tools in teachers of the FCEH - UNAP Iquitos 2023. This study is descriptive of field study, contemporary transactional, and univariate designs. The object of study was established by 140 teachers with a non-probabilistic sample of 60. A referential population of 1678 students with a probabilistic sample with proportional allocation of 313. Data was collected through a valid and reliable questionnaire. The results show the mean of the study population was 65,546 and of the reference population was 55,392, the categories of study population and reference population, as well as the percentages. It was concluded that the use of digital tools in the object of study is adequate. On the other hand, according to the students as a referential population, they concluded that the use of digital tools is inadequate.